Rare earth permanent magnets in Russia’s wind power - Oleg Valerievich Zhdaneev; Konstantin Nikolaevich Frolov; Valeriy Anatolievich Kryukov; Victor Anatolievich Yatsenko (Materials Science for Energy Technologies, 2024)
Today, the world’s power system is in transition towards “green” generation in line with the Paris climate agreement of 2015. Emergence of this technology alters existing consumption pattern for mineral resources. Today, center stage is taken by such crucial elements as copper, nickel, lithium, cobalt and, of course, REMs. Permanent REM magnets are pivotal to transition to green and renewable energy. Therefore, in new circumstances the global power system needs different approaches to production and supply chains for key natural resources. Russia’s FEC is the world’s second largest (after the USA) producer of power resources and third largest in-country consumer of the same (trailing the USA and China). However, there is no full-cycle production of individual REMs and REM-based alloys inside the country, despite one of the largest mineral resource bases of REMs in the world. A clearly apparent global trend shows that the pace of developing new MR sources and the necessary investments do not match acceleration in production of such high tech products as solar batteries, wind power generators (WPG), and electric cars. This is due to the fact that many key MRs (especially REMs) come from a small number of producers located in just a few countries. With this in mind, the paper presents a study of the production chain of NdFeB magnets and electric engines based on them, seen as essential to development of Russia’s wind power. Also, economic feasibility of some generation technologies in connection with the ever-increasing power of generators is considered. Basic topologies of electric machines are analyzed as well. The key question of the study is whether rare earth MRs become an incentive for transition to a new energy system in Russia or a bottleneck in the process.